2007
DOI: 10.1001/archopht.125.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Genetic Loci for Intraocular Pressure

Abstract: To identify genetic loci that control intraocular pressure (IOP). Methods: We performed a genomewide scan of IOP, using 486 pedigrees ascertained through a populationbased cohort, the Beaver Dam Eye Study. Linkage analysis was performed using the modified Haseman-Elston regression models and variance components linkage analysis. Results: Seven regions of interest were identified on chromosomes 2, 5, 6, 7, 12, 15, and 19. The novel linkage region on chromosome 19p had an empirical multipoint P value of 6.1ϫ10 −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…137 In the context of establishing a genetic correlation between POAG endophenotypes and POAG, a genome-wide scan of IOP was performed, using 486 pedigrees ascertained through a population-based cohort, the Beaver Dam Eye Study. 138 The investigators' purpose was to identify quantitative trait loci controlling IOP and thereby influencing the development of glaucoma. Seven loci of interest were identified (2, 5, 6, 7, 12, 15, and 19) and two of the regions (on chromosomes 2 and 19) co-localized with blood pressure loci.…”
Section: The Role Of Endophenotypes In Glaucomamentioning
confidence: 99%
“…137 In the context of establishing a genetic correlation between POAG endophenotypes and POAG, a genome-wide scan of IOP was performed, using 486 pedigrees ascertained through a population-based cohort, the Beaver Dam Eye Study. 138 The investigators' purpose was to identify quantitative trait loci controlling IOP and thereby influencing the development of glaucoma. Seven loci of interest were identified (2, 5, 6, 7, 12, 15, and 19) and two of the regions (on chromosomes 2 and 19) co-localized with blood pressure loci.…”
Section: The Role Of Endophenotypes In Glaucomamentioning
confidence: 99%
“…167 These loci may control both systemic pressure reflected in the eye and in the vascular system. 166 This observation is the novel beginning of a journey that could lead to the discovery of those genes associated with the control of IOP, which may help in the selection of therapy that can more effectively halt disease progression. 168 …”
Section: A Bold New Step Toward Antiglaucoma Treatment: Genetic Identmentioning
confidence: 99%
“…A commingling analysis from the Australian Blue Mountains Eye Study suggested the presence of a major gene contributing to 18% of the variance of IOP 10. Novel genetic loci for IOP have been identified,8 1113 but not yet replicated. The complexity of the phenotypic definition of glaucoma has contributed to the difficulties in identifying genes involved in this disease 14…”
mentioning
confidence: 99%